POTRET STRATEGI DAN KEBIJAKAN PEMERINTAH DALAM MENGATASI MASALAH PENGANGGURAN DI INDONESIA: TINJAUAN STUDI LITERATUR - Lusiana, Dewi; Moh Badrul Qomar; Aldi Setiadi (Jurnal Liabilitas, 2024)
Unemployment is still a major problem in Indonesia. Although the government has made several efforts to address the unemployment problem, the fact is that this problem is still not resolved. This study aims to reanalyze how the government's efforts in overcoming unemployment in Indonesia are based on its strategies and policies. The method used in research is the study of literature. The results of the study explain that there are several efforts as strategies and policies that can be carried out by the government in overcoming the unemployment problem, namely improving the education system, creating jobs, providing accurate and transparent job information, organizing job training programs, developing marine potential and simplifying investment licensing. Given that the problem of unemployment is not only caused from one dimension, the government needs to solve the problem of unemployment from various dimensions. Keyword: Problem Unemployment, Government Strategy and Policy.